2014
DOI: 10.4102/sajhivmed.v15i3.9
|View full text |Cite
|
Sign up to set email alerts
|

Management of patients presenting with diarrhoea to a regional emergency department in KwaZulu-Natal: Call for clearer, more relevant guidance

Abstract: Background. HIV is prevalent throughout South Africa, and diarrhoea is a common presentation to the emergency department (ED) among both HIV-infected and -uninfected individuals. Method. We audited the management of diarrhoea against standard guidelines in the ED of a regional hospital in KwaZulu-Natal. Patients presenting with diarrhoea as their chief complaint were eligible and data were collected prospectively. Results. A total of 72 patients were included: 58 (81%) of patients were HIV-positive with an ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…South African National Department of Health guidelines for the treatment of diarrhoea are included in the standard treatment guidelines and essential medicines list (hospital and primary healthcare levels) [ 4 , 5 ]. An audit at a provincial hospital in KwaZulu-Natal found that patients with diarrhoea were managed inconsistently, specifically with regards to antibiotic treatment, which could result in an increased risk of antibiotic resistance and infection with Clostridioides difficile (C. difficile) [ 6 ]. The study reported that stool samples were submitted for routine microscopy (examination for ova and parasites) and culture in 47% of cases, yet 60% of cases were treated with antibiotics (only 35% of which had positive culture results).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…South African National Department of Health guidelines for the treatment of diarrhoea are included in the standard treatment guidelines and essential medicines list (hospital and primary healthcare levels) [ 4 , 5 ]. An audit at a provincial hospital in KwaZulu-Natal found that patients with diarrhoea were managed inconsistently, specifically with regards to antibiotic treatment, which could result in an increased risk of antibiotic resistance and infection with Clostridioides difficile (C. difficile) [ 6 ]. The study reported that stool samples were submitted for routine microscopy (examination for ova and parasites) and culture in 47% of cases, yet 60% of cases were treated with antibiotics (only 35% of which had positive culture results).…”
Section: Introductionmentioning
confidence: 99%
“…The study reported that stool samples were submitted for routine microscopy (examination for ova and parasites) and culture in 47% of cases, yet 60% of cases were treated with antibiotics (only 35% of which had positive culture results). The authors called for clearer national guidelines for the management of diarrhoea, particularly for HIV-infected patients who comprised the majority (81%) of diarrhoeal cases presenting to the emergency department [ 6 ]. Robust epidemiological and aetiological data are needed to formulate nationally relevant guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…In patients presenting to the Emergency department with a chief complaint of diarrhea, a South African study conducted by Kudsk-Iversen et al, showed that 60% of these patients received antibiotics, yet only 34% had an organism identified on stool microscopy or culture. In all cases, the final diagnosis was listed as acute gastroenteritis without further specification and antibiotic use according to national guidelines appeared inconsistent 15 .…”
Section: Introductionmentioning
confidence: 99%